Promoting Innovative Behavior in Employees: The Mechanism of Leader Psychological Capital - Wang, Yanfei; Chen, Yi; Zhu, Yu (Frontiers in Psychology, 2021)
The study reported in this paper analyzed the influence of leader psychological capital (PsyCap) on employees’ innovative behavior and the roles of psychological safety and growth need strength (GNS) in this process within the context of positive psychology theory and conservation of resources theory. Three stages of questionnaire surveys were administered to 81 enterprise leaders and their 342 direct subordinates in South China to test our theoretical model. The results showed that leader PsyCap had significant and positive effects on employee innovative behavior, psychological safety had a partially mediating effect, and GNS positively moderated the relationship between psychological safety and innovative behavior. The results revealed the mechanism of PsyCap and external boundary conditions of the influence of leader PsyCap on employee innovative behavior. The study expands the research results of leader PsyCap theory, and also provides guidance on how enterprises manage employees’ innovative behavior.